Determination of microbiological quality of vegetables irrigated with Kano Abattoir wastewater (Journal of Tropical Resources and Sustainable Science (JTRSS), 2021)
Microbiological contamination of vegetables occurs directly along the food chain resulting in a serious Health problem and consequently leading to death during the acute phase of the microbial infection. A total of 15 different samples were randomly purchased and analyzed for the presence of enteropathogenic organisms. Enumeration of aerobic mesophilic bacteria, fungi and coliform counts were carried out using standard procedures which is the use of most probable numbers (MPN). Isolation and identification of some pathogens was also carried out using standard procedures. The mean count of all the three (3) different samples (cucumber, tomato and lettuce) were exceeded the maximum acceptable limit (105cfu/g/ml) set by the Food and Agricultural Organizations (FAO). The highest mean count for both bacteria and fungi in all the 15 samples; cucumber with 1.52x105 cfu/g of bacteria and 1.01x105 cfu/g of fungi, tomato with 1.34x105 cfu/g of bacteria and 1.06x105 cfu/g of fungal, whereas, lettuce with 1.18x105 and 1.29x105 of bacteria and fungi respectively. Out of 15 different samples examined the occurrence of enteropathogenic organisms in all the sample were found to be 65% of cucumber while tomato had 60% followed by lettuce with 60%. This shows that cucumber samples are more contaminated due to the higher percentage of occurrence the enteropathogenic organisms in it. The results indicated that the vegetable samples examined in this study did not meet bacteriological quality standards. The implications of the results on human and environmental health are discussed.
Keywords: Enteropathogenic; bacteria; fungi; Coliform count; cucumber; tomato; lettuce